Fabrication and Characterization of the PMMA/G/Ag Nanocomposite by Pulsed Laser Ablation (PLAL) - Musaab Khudhur Mohammed; Ghaleb Al-Dahash; Amer Al-Nafiey (Nano Biomedicine and Engineering, 2022)
In this work, By using the laser ablation technique (PLAL) to fabricate novel PMMA/G/Ag nanocomposites with less laser energy and short time ablation and study the structural, morphological and optical properties. The X-ray diffraction (XRD) confirmed that the GNPs and AgNPs in the PMMA matrix have a crystallite size increased with increasing the pulse number. Also, the SEM images confirm the homogeneous distribution of the GNPs and AgNPs in the PMMA matrix and the sizes of particles in the nanoscale. Additionally, the link between GNPs and AgNPs in the polymer matrix has been confirmed by the FTIR. Moreover, UV-VIS spectroscopy was studied and confirm the nanocomposite has optical properties with the presence of the polymer as a host and calculating the optical energy gap. For that, this novel nanocomposite with these properties promising for many applications. Finally, the study proved that the PLAL is very suitable for decorated graphene and metal on the polymer matrix with lower pulse laser energy and short ablation time.